2019
DOI: 10.1080/1828051x.2018.1503043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polyphenols on the performance and antioxidant status of sows and piglets

Abstract: ABSRACTThe aim of this study was to determine the efficacy of polyphenols in pigs. The experiment was performed on 52 sows divided into 4 groups. Untreated control sows (group 1) were not administered vitamin E in the premixes. The diets of the experimental animals were supplemented with vitamin E in the amount of 50 mg (group 2) or 100 mg/kg diets (group 3) (gestation diets) and 75 mg (group 2) or 150 mg/kg diets (group 3) (lactation diets). The diets of group four sows were supplemented with vitamin E (50/75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Lower serum MDA level in laying hens fed with thyme and rosemary dry leaf powder as source of phenolic compounds at 0.9% level was also reported [ 50 ]. The replacement of 50% dietary vitamin E with polyphenols did not alter the growth performance but could improve the antioxidant status of sows or their offspring [ 73 ]. In piglets, dietary supplementation of polyphenol mixture originated from apples, grape seeds, green tea leaves and olive leaves could reduce plasma MDA value [ 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lower serum MDA level in laying hens fed with thyme and rosemary dry leaf powder as source of phenolic compounds at 0.9% level was also reported [ 50 ]. The replacement of 50% dietary vitamin E with polyphenols did not alter the growth performance but could improve the antioxidant status of sows or their offspring [ 73 ]. In piglets, dietary supplementation of polyphenol mixture originated from apples, grape seeds, green tea leaves and olive leaves could reduce plasma MDA value [ 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…The comparatively poorer growth of GP during the pre-weaning period [3] can partially be attributed to the lower milk yield of the gilt [8,9], meaning that reducing oxidative stress in lactating gilts may be a useful management strategy for increasing productivity in GP. This was demonstrated by Lipiński et al [10], who observed antioxidant polyphenol supplementation improved litter and body weights at weaning. Polyphenols are secondary plant metabolites that exhibit anti-oxidative effects [11].…”
Section: Introductionmentioning
confidence: 69%
“…The determination of the active compounds of U. tomentosa , T. parthenium and B. serrata was performed by the supplier (A.C.E.F. Fiorenzuola d’Arda, Italy) using high-performance liquid chromatography (HPLC) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that dietary plant polyphenols in piglets enhance blood antioxidant status [ 14 , 15 ]. However, some studies report no improvements in the markers related to antioxidant status due to supplementation with polyphenols [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%